Ethik in Beziehungen. Im Gespräch mit Hans-Joachim Höhns „Konturen einer Tugendethik“ - Meyer zu Hörste-Bührer, Raphaela (Gott – Welt – Mensch, Eine Auseinandersetzung mit Hans-Joachim Höhn)

On the Impact of Basic Mutation Operators and Populations within Evolutionary Algorithms for the Dynamic Weighted Traveling Salesperson Problem - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Evolutionary algorithms have been shown to obtain good solutions for complex optimization problems in static and dynamic environments. It is important to understand the behaviour of evolutionary algorithms for complex optimization problems that also involve dynamic and/or stochastic components in a systematic way in order to further increase their applicability to real-world problems. We investigate the node weighted traveling salesperson problem (W-TSP), which provides an abstraction of a wide range of weighted TSP problems, in dynamic settings. In the dynamic setting of the problem, items that have to be collected as part of a TSP tour change over time. We first present a dynamic setup for the dynamic W-TSP parameterized by different types of changes that are applied to the set of items to be collected when traversing the tour. Our first experimental investigations study the impact of such changes on resulting optimized tours in order to provide structural insights of optimization solutions. Afterwards, we investigate simple mutation-based evolutionary algorithms and study the impact of the mutation operators and the use of populations with dealing with the dynamic changes to the node weights of the problem.
Keywords: dynamic optimization; evolutionary algorithms; re-optimization; weighted traveling salesperson problem

Runtime Analysis of Quality Diversity Algorithms - Bossek, Jakob; Sudholt, Dirk (Proceedings of the Genetic and Evolutionary Computation Conference)
Quality diversity (QD) is a branch of evolutionary computation that gained increasing interest in recent years. The Map-Elites QD approach defines a feature space, i.e., a partition of the search space, and stores the best solution for each cell of this space. We study a simple QD algorithm in the context of pseudo-Boolean optimisation on the "number of ones" feature space, where the ith cell stores the best solution amongst those with a number of ones in [(i - 1)k, ik - 1]. Here k is a granularity parameter 1 {$≤$} k {$≤$} n+1. We give a tight bound on the expected time until all cells are covered for arbitrary fitness functions and for all k and analyse the expected optimisation time of QD on OneMax and other problems whose structure aligns favourably with the feature space. On combinatorial problems we show that QD finds a (1 - 1/e)-approximation when maximising any monotone sub-modular function with a single uniform cardinality constraint efficiently. Defining the feature space as the number of connected components of a connected graph, we show that QD finds a minimum spanning tree in expected polynomial time.
Keywords: quality diversity; runtime analysis

Generating Diverse and Discriminatory Knapsack Instances by Searching for Novelty in Variable Dimensions of Feature-Space - Marrero, Alejandro; Segredo, Eduardo; Hart, Emma; Bossek, Jakob; Neumann, Aneta (Proceedings of the Genetic} and Evolutionary Computation Conference)
Generating new instances via evolutionary methods is commonly used to create new benchmarking data-sets, with a focus on attempting to cover an instance-space as completely as possible. Recent approaches have exploited Quality-Diversity methods to evolve sets of instances that are both diverse and discriminatory with respect to a portfolio of solvers, but these methods can be challenging when attempting to find diversity in a high-dimensional feature-space. We address this issue by training a model based on Principal Component Analysis on existing instances to create a low-dimension projection of the high-dimension feature-vectors, and then apply Novelty Search directly in the new low-dimension space. We conduct experiments to evolve diverse and discriminatory instances of Knapsack Problems, comparing the use of Novelty Search in the original feature-space to using Novelty Search in a low-dimensional projection, and repeat over a given set of dimensions. We find that the methods are complementary: if treated as an ensemble, they collectively provide increased coverage of the space. Specifically, searching for novelty in a low-dimension space contributes 56% of the filled regions of the space, while searching directly in the feature-space covers the remaining 44%.
Keywords: evolutionary computation; instance generation; instance-space analysis; knapsack problem; novelty search

Do Additional Target Points Speed Up Evolutionary Algorithms? - Bossek, Jakob; Sudholt, Dirk (Theoretical Computer Science)
Most runtime analyses of randomised search heuristics focus on the expected number of function evaluations to find a unique global optimum. We ask a fundamental question: if additional search points are declared optimal, or declared as desirable target points, do these additional optima speed up evolutionary algorithms? More formally, we analyse the expected hitting time of a target set OPT{$\cup$}S where S is a set of non-optimal search points and OPT is the set of optima and compare it to the expected hitting time of OPT. We show that the answer to our question depends on the number and placement of search points in S. For all black-box algorithms and all fitness functions with polynomial expected optimisation times we show that, if additional optima are placed randomly, even an exponential number of optima has a negligible effect on the expected optimisation time. Considering Hamming balls around all global optima gives an easier target for some algorithms and functions and can shift the phase transition with respect to offspring population sizes in the (1,{$λ$}) EA on OneMax. However, for the one-dimensional Ising model the time to reach Hamming balls of radius (1/2-{$ϵ$})n around optima does not reduce the asymptotic expected optimisation time in the worst case. Finally, on functions where search trajectories typically join in a single search point, turning one search point into an optimum drastically reduces the expected optimisation time.
Keywords: Evolutionary algorithms; pseudo-Boolean functions; runtime analysis

On Single-Objective Sub-Graph-Based Mutation for Solving the Bi-Objective Minimum Spanning Tree Problem - Bossek, Jakob; Grimme, Christian (Evolutionary Computation)
We contribute to the efficient approximation of the Pareto-set for the classical NP-hard multi-objective minimum spanning tree problem (moMST) adopting evolutionary computation. More precisely, by building upon preliminary work, we analyse the neighborhood structure of Pareto-optimal spanning trees and design several highly biased sub-graph-based mutation operators founded on the gained insights. In a nutshell, these operators replace (un)connected sub-trees of candidate solutions with locally optimal sub-trees. The latter (biased) step is realized by applying Kruskal’s single-objective MST algorithm to a weighted sum scalarization of a sub-graph.We prove runtime complexity results for the introduced operators and investigate the desirable Pareto-beneficial property. This property states that mutants cannot be dominated by their parent. Moreover, we perform an extensive experimental benchmark study to showcase the operator’s practical suitability. Our results confirm that the subgraph based operators beat baseline algorithms from the literature even with severely restricted computational budget in terms of function evaluations on four different classes of complete graphs with different shapes of the Pareto-front.

Begriffliches Verständnis von Grundschüler*innen zur Achsensymmetrie - Wallner, Melina (Grundlegende Kompetenzen sichern: Lernende und Lehrende im Blick)
Dieser Tagungsband dokumentiert die Ergebnisse der 30. Jahrestagung des Arbeitskreises Grundschule in der Gesellschaft für Didaktik der Mathematik (GDM), die dieses Mal vom 17. bis zum 19. November 2023 an der Universität Bremen stattfand. Die Tagung stand unter dem Thema ‚Grundlegende Kompetenzen sichern: Lernende und Lehrende im Blick‘. Die Tagung greift damit die immer wieder aktuelle Frage auf, wie der Mathematikunterricht der Grundschule gestaltet werden kann, so dass alle Kinder grundlegende Kompetenzen erwerben und über diese auch sicher und langfristig verfügen. Empirische Studien wie etwa der IQB-Bildungstrend zeigen, dass der Anteil an Kindern, die diese Kompetenzen, die unbestritten für das Weiterlernen in den darauffolgenden Schuljahren und im Beruf relevant sind, am Ende ihrer Grundschulzeit (noch) nicht besitzen, größer wird. Weiter setzten sich acht Arbeitsgruppen mit den Themenfeldern ‚Arithmetik‘, ‚Geometrie‘, ‚Sachrechnen‘, ‚Daten, Zufall und Wahrscheinlichkeit‘, ‚Kommunikation & Kooperation‘, ‚PriMaMedien: Lernen, Lehren und Forschen mit digitalen Medien‘, ‚Frühe mathematische Bildung‘ sowie ‚Lehrkräftebildung‘ intensiv mit aktuellen Forschungs- und Praxisfragen auseinander. Die zentralen Inhalte der Arbeitsgruppen sind in diesem Band ebenfalls dokumentiert.

Expertise and professionalism for inclusive (mathematics) teaching and learning: reflections on findings from interdisciplinary professionalisation research - Seitz, Simone; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (Teachers and Teaching)

„Fotos, die jede:r kennt“ Eine empirische Untersuchung historischer Kenntnisse anhand von Bildikonen bei Studierenden des Lehramts Geschichte - Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Geschichtsdidaktisch intervenieren. Beiträge zur Forschungswerkstatt „Geschichtsdidaktik Empirisch“ 2020)

Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

Geometric-phase metalens to be used for tunable optical tweezers in microfluidics - Geromel, René; Rennerich, Roman; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Geometric-phase dielectric meta-lenses made of silicon with high numerical aperture and short focal lengths are fabricated and characterised. For circularly polarised light, the same meta-lens can act as a converging or diverging lens, depending on the handedness of the circular polarisation. This effect enables application for optical tweezers that trap or release µm-size polymer beads floating in a microfluidic channel on demand. An electrically addressable polarisation converter based on liquid crystals may be used to switch between the two states of polarisation, at which the light transmitted through the meta-lens is focused (trapping) or defocussed (releasing), respectively.

Luminescent DNA-origami nano-rods dispersed in a lyotropic chromonic liquid crystal - Zhang, Bingru; Nguyen, Linh; Martens, Kevin; Heuer-Jungemann, Amelie; Philipp, Julian; Kempter, Susanne; Rädler, Joachim O.; Liedl, Tim; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann.

Der Neue Weltengarten. Jahrbuch für Literatur und Interkulturalität 2022

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

KI-basierte Extrahierung von Anforderungen aus Regularien für die Automobilentwicklung - Gräßler, Iris; Özcan, Deniz; Preuß, Daniel (Design fox X - Beiträge zum 34. DfX-Symposium)

Structural fingerprints in the reflectance anisotropy of AlInP(001) - Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Hannappel, Thomas; Schmidt, Wolf Gero (Physical Review B)

Poster: Towards Practical Brainwave-based User Authentication - Fallahi, Matin; Arias Cabarcos, Patricia; Strufe, Thorsten (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

Simone Atangana Bekono: Salomés Zorn (NL: Confrontaties) - Lammer, Christina

Sichtbarer Euklid? Zur Geometrisierung des Bildes in "De pictura" - Siemoneit, Johannes Gabriel (Leon Battista Alberti, "De pictura" (lat.). Kunsttheorie – Rhetorik – Narrative / Teoria dell'arte, retorica, narrative)